Application of bandura's social cognitive theory to examine the factors that motivate undergraduate student's participation in service-learning environment - Caroline Gerard, Anthony Gerard (2019)
Service-learning is a mutual effort between the public and students to solve the problems that they face whilst improving the community. Students are increasingly participating in service-learning programs as it holds many beneficial prospects for them. Although there was a significant spike in student’s participation in service-learning programs, there was still a lack of research done on why students are motivated to participate in the programs. Additionally, very few notable studies have explored the issue using undergraduate students and have yet to explore the factors that motivate undergraduate students to participate in service-learning programs in Malaysia. Therefore, this study focused on exploring the personal and environmental factors that motivate undergraduate student’s participation in service-learning programs. Albert Bandura’s Social Cognitive Theory (SCT) (1986) was used to guide this study. Furthermore, twenty-five undergraduate students were selected using snowball sampling method as interviewees for the in-depth interviews. The results indicated personal factors that motivated undergraduate students were due to opportunities for self and skill development, self-satisfaction, personal achievement as well as need to obtain academic excellence, to gain knowledge and course requirement. On the other hand, environmental factors which motivated undergraduate students were peer encouragement, sense of belongingness and the strong belief in karma, cultural traditions as well as the religious upbringing of their families. The limitations of this study are due to the nature of the qualitative research whereby it mainly focused on a centralized sample which limited this research to obtain findings from a generalized population of undergraduate students. Therefore, mixed methods should be utilized to overcome this limitation. Finally, the findings of this research held great significance for undergraduate students, higher learning institutions and for future researchers.